2013
DOI: 10.1371/journal.pone.0060833
|View full text |Cite
|
Sign up to set email alerts
|

Association between Glutathione S-Transferase T1 Null Genotype and Gastric Cancer Risk: A Meta-Analysis of 48 Studies

Abstract: BackgroundGlutathione S-transferases (GSTs) have proved to be involved in the detoxifying several carcinogens and may play an important role in carcinogenesis of cancer. Previous studies on the association between Glutathione S-transferase T1 (GSTT1) polymorphism and gastric cancer risk reported inconclusive results. To clarify the possible association, we conducted a meta-analysis of eligible studies.MethodsWe searched in the Pubmed, Embase, and Wangfang Medicine databases for studies assessing the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…GSTM1 and GSTT1 null genotypes were associated with statistically significant increased risk in recent meta-analyses that include Asian studies. 11,12 In our study, the point estimates of ORs for GSTM1 and GSTT1 null genotypes on the gastric cancer risk were above unity, which was similar to those of previous studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…GSTM1 and GSTT1 null genotypes were associated with statistically significant increased risk in recent meta-analyses that include Asian studies. 11,12 In our study, the point estimates of ORs for GSTM1 and GSTT1 null genotypes on the gastric cancer risk were above unity, which was similar to those of previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…9,10 In recent several metaanalyses, GSTM1 and GSTT1 null genotypes, which cannot detoxify reactive carcinogens, were associated with increased risk of gastric cancer. 11,12 Although the association between CYP1A1 (rs4646903 and rs1048943) polymorphisms, which are common single nucleotide polymorphisms (SNPs), and gastric cancer risk was not found, 13,14 another study showed that CYP1A1 (rs4646903) mutational heterozygous genotype was associated with a statistically significant increased risk compared with wild genotype among large sample size studies only. 15 Most individual studies in these meta-analyses and recently published studies are retrospective, and their sample sizes are small.…”
mentioning
confidence: 99%
“…It is known that deletions in GSTM1 and GSTT1 genes is associated with reduced or absence of enzyme activity (Hallier et al 1993 ). Moreover, numerous studies have shown the link between the lack of enzyme activity in GSTM1 and GSTT1 and the susceptibility to develop various types of cancer, such as oral cancer, gastric cancer, bladder cancer, and CML in different ethnical groups worldwide (Bajpai et al 2007 ; Sharma et al 2013 ; Dunna et al 2013 ; Ma et al 2013 ; Dong et al 2013 ; Bhat et al 2012 ). Furthermore, other studies have found an association between GSTM1 and GSTT1 deletions and the response to chemotherapy, such as disease free survival, overall survival or toxicity (Voso et al 2002 ; Mossallam et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…The frequencies of homozygous deletions of GSTT1 gene are higher in Asians and Africans than in Caucasians], whereas homozygous deletions of GSTM1 gene are higher in Caucasians and Asians than in Africans (12,13) . Moreover, numerous studies have evaluated the association between polymorphisms of GSTs gene and the susceptibility to develop various types of cancer, such as gastric cancer, oral cancer, bladder cancer, and chronic myeloid leukemia CML in different ethnical groups worldwide (14)(15)(16)(17) . Furthermore, other studies have found an association between GSTM1 and GSTT1 deletions and disease susceptibility, drug response and resistance to chemotherapy treatment (18)(19)(20) .…”
Section: Introductionmentioning
confidence: 99%